The interplay of dynamic capabilities and innovation output in family and non-family companies: The moderating effect of environmental dynamism - Tomasz Ingram; Teresa Kraśnicka (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: In the article, we aim to test the relationship between dynamic capabilities (DCs) and innovation output as moderated by environmental dynamism and establish if there are significant differences between family and non-family firms in this regard. Research Design & Methods: To test three research hypotheses we employed quantitative research methodology. Our results are based on the data from 211 family and 211 non-family companies from the Polish post-transition economy. Results were analyzed using multigroup structural equation modelling. Findings: Results indicate that DCs can be justifiably perceived in two dimensions (sensing and seizing; reconfiguring) and these dimensions influence the innovation output in both family and non-family businesses, however, this impact varies. The environmental dynamism does not significantly moderate the basic relationship, but it influences the level of innovation output in non-family businesses. Models estimated for family and non-family businesses are significantly different, which proves that subtle differences between these two groups of companies exist. Implications & Recommendations: In the article, we enrich the theory of innovation in family firms and show how subtle differences create a different portrait of relationships between DCs and innovation in these types of companies. Contribution & Value Added: To our knowledge, it is the first study to show how family businesses are different from their non-family counterparts with respect to relationships between DCs and innovation output as measured by the number of new products and solutions.
Keywords: O30; 330; dynamic capabilities; environmental dynamism; family business; structural equation modelling